Bacillus velezensis T971 genome informs starch degradation in tobacco - Hu, Liwei; Zhang, Xinpeng; Gao, Qin; Yang, Mengmeng; Dong, Xiangzhou; Cheng, Tingming; Liang, Taibo; Yang, Bingye; Zhang, Yanling; Yin, Yanbin (Frontiers in Microbiology, 2025)
Starch is an important reserve polysaccharide in tobacco leaves. An endophytic bacterium, Bacillus velezensis T971, was isolated from the leaves of Nicotiana tabacum L. Yunyan 97 and showed strong starch-degrading activity on the agar plate containing 1% starch (w/v). The complete genome of T971 was determined using PacBio long-read sequencing technology, revealing a single circular chromosome of 3,930,941 bp encoding 3,692 proteins. The T971 genome was compared with 242 other complete genomes of B. velezensis. Pan-genome analysis revealed a sporadic distribution of the plantazolicin (PZN) biosynthetic gene cluster (BGC) and mobile genetic elements (MGEs) (e.g., genomic islands (GIs) and prophages), which have contributed to the variability of B. velezensis genomes. Carbohydrate-active enzyme (CAZyme) analysis found 113 CAZymes in the T971 genome, including 41 glycoside hydrolases (GHs), 40 glycosyltransferases (GTs), and 14 carbohydrate esterases (CEs). One (GH13_28 family) of the four α-amylases is the most promising candidate for starch degradation in tobacco leaves, possessing a signal peptide and two carbohydrate-binding modules (CBMs). This study identifies B. velezensis T971 as a potential strain for industrial amylase production.